Independent component analysis : principles and practice - Roberts, Stephen; Everson, Richard (Cambridge : New York : Cambridge University Press, 2001)
Independent Component Analysis is an important tool for modelling and understanding empirical datasets consisting of mixtures of independent sources. This book contains papers by leading researchers on the subject. The theory is reviewed and many applications are described. Ideal for researchers and graduate students in the field.
Includes bibliographical references and index.
Keywords: Neural networks (Computer science).; Independent component analysis